Assessment of the effectiveness of strategic personnel management of the company - Kryshtanovych, Myroslav Frankovich; Kapitanets, Svitlana Volodymyrivna; Filina, Svitlana Volodymyrivna; Oleksiuk, Nataliya Stepanivna; Prodius, Oksana Ivanivna (Academy of Strategic Management Journal, 2019)
Сучасне бізнес середовище стає все більш динамічним, а концепція стратегічного управління персоналом привертає увагу у корпоративному світі та в науковому співтоваристві. Це дослідження спрямоване на аналіз практики та оцінку ефективності управління персоналом у системі стратегічного управління персоналом компанії. Щоб досягти цього, було порівняно теоретичні припущення з емпіричними методами тестування. У цьому дослідженні використано методи оцінки, що дозволило визначити систему коефіцієнтів для оцінки ефективності управління персоналом компанії. Виявлені результати: розробка та реалізація стратегій управління персоналом вимагає узгодження інтересів керівництва та керівників компанії та підзвітності керівництва; для оцінки ефективності стратегічного управління персоналом компанії доцільно використовувати якісні та кількісні показники; оцінка персоналу компанії визначає ключову роль професійної компетентності для підвищення ефективності використання людських ресурсів.

The modern business environment becomes increasingly dynamic, and the concept of strategic personnel management attracts attention in the corporate world and in scientific community. This study is aimed at analyzing the practice and assessing the effectiveness of personnel management in the company's strategic human resources management system. In order to achieve this, the authors compared theoretical thinking with empirical testing methods. In this study, expert used assessment methods, which made it possible to determine a system of coefficients for assessing the effectiveness of company’s personnel management. Revealed results: development and implementation of personnel management strategies requires the coordination of the interests of management and company’s leaders and management accountability, for the assessment of the effectiveness of strategic personnel management of the company, it is advisable to use qualitative and quantitative indicators; assessment of company’s personnel determines the key role of professional competence for improvement of the effectiveness of human resources use.
Keywords: personnel; personnel management; human resources (HR) management; effectiveness of personnel management; персонал; управління персоналом; управління персоналом (HR); ефективність управління персоналом